LEVOSIMENDAN IN TREATMENT OF CONGENITAL AND ACQUIRED HEART DISEASES. Issue 1 (14th December 2015) - Dinarević, Senka; Jonuzi, Fedzat; Halimic, Mirza; Begic, Zijo; Kadić, Almira; Gojak, Refet
Abstract : Introduction: Levosimendan as a new generation vasoactive coronary and peripheral dilatation drug, has been recently developed for cardiac decompensation treatment. Aim: To evaluate the effects on cardiac function during treatment with Levosimendan in cardiac decompensated severely ill infants and children. Methods: Retrospective-prospective study was performed in Paediatric Clinic CC University of Sarajevo, from 01.01.2013. till 30.12.2014. Study included 7 pts; with congenital/post surgery Tetralogia Fallot/ and acquired heart diseases/dilated cardiomyopathy-myocarditis/pts. Patients were divided into two groups: I Group pre treatment and II Group, post Levosimendan treatment. Parameters evaluated were: age, sex, diagnosis, left ventricle EF /LV EF/pre and post-treatment (EF1 and EF2/and use of inotropic drugs. Results: The evaluated variables were: age in I Group of pts /4/ with congenital heart disease: mean 7.5 months/ratio: 6.5–8.5 months of age/and in second with acquired heart diseases /3/, mean: 8.5 years of age/3–14 years/, 3 boys; inotropic drugs used in both Groups of pts: Noradrenalin, Dobutamin, Dopamine and Corotrop which were decreased and stopped in the First Group 2nd day post Levosimendan start and in second Group, 3rd day stopped post Levosimendan start. LV EF evaluated in both Groups; difference of mean EF1 in relation to mean EF2 values, showed statistically significant improvement of LV function /p=0, 002/ and decrease in inotropic support. Conclusion: Levosimendan has positive effects on myocardial function restoration regardless on congenital or acquired heart diseases in paediatric population as well as in decrease in inotropic support and rapid myocardial cell recovery.